2018
DOI: 10.1111/opo.12568
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve tissue displacement during mild intraocular pressure elevation: its relationship to central corneal thickness and corneal hysteresis

Abstract: Mild acute elevation of IOP produces large and rapidly reversible shifts in optic nerve tissue in young, healthy eyes. The resulting degree, direction and spatial distribution of cup movement are associated with IOP status and corneal thickness, but not corneal hysteresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[ 36 ] As we have demonstrated that the sectoral characteristics of CCT negatively correlate with peripapillary capillary dropout, we hypothesize that a thinner cornea may directly provoke any change in IOP and increase the susceptibility of glaucoma. Consistently, our results agree with the findings of Bedggood et al [ 36 ] which show that a thinner CCT correlates with a decrease in inferior sectoral peripapillary vessel density in NTG.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] As we have demonstrated that the sectoral characteristics of CCT negatively correlate with peripapillary capillary dropout, we hypothesize that a thinner cornea may directly provoke any change in IOP and increase the susceptibility of glaucoma. Consistently, our results agree with the findings of Bedggood et al [ 36 ] which show that a thinner CCT correlates with a decrease in inferior sectoral peripapillary vessel density in NTG.…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) has emerged over the last decade as the most widely used tool to image the ONH in vivo [8][9][10][11][12][13][14][15][16][17]. OCT allows acquiring three-dimensional (3D) volumes of the ONH with µm-scale resolution, and with sufficient signal penetration to visualize the lamina cribrosa region within the ONH.…”
Section: Introductionmentioning
confidence: 99%